Is less more? Dismantling imaginal retraining and examining the effects of psychoeducation and embodied cognition on craving and alcohol consumption in problem drinkers: A randomized controlled trial. (December 2022) - Wirtz, Janina; Moritz, Steffen; Gehlenborg, Josefine; Ascone, Leonie; Kühn, Simone
Highlights: A simplified version of the technique renders consistent results for craving reduction. No effects were observed for imaginal retraining on drinking amount. Emotion induction via thoughts, imagery, and postures may be dispensable. Other forms of instruction (such as a video format) should be considered. Imaginal retraining's core effective component might be the arm movement. Abstract: Background: Imaginal retraining, a type of approach-bias-modification performed in one's own imagination, is effective in reducing alcohol craving in problem drinkers. This study aims to segregate three main components of the original technique and compare their effectiveness in reducing craving and alcohol consumption. Methods: The study was conducted online. Interested individuals wishing to reduce their alcohol consumption underwent a baseline assessment (T0), whereby a total of N = 200 included participants were randomly assigned to one of four study arms. There were three active groups receiving different training manuals: psychoeducation + advice only (PE), PE + a simplified motor in-sensu AAT instruction (AAT0), and the 'enriched' original imaginal retraining technique (including the components PE + enhanced movements + an embodied cognition/ emotion induction instruction) (AAT+), vs. a wait-list control (WLC). Participants in the three active arms were instructed to train twice a day (10 mins. each) over the course of four weeks, whereafter a post-test was conducted (T1). A follow-up took place one month later (T2). Repeated measures ANOVAs were computed to test for differential changes of the four groups over time (group*time interaction effects) concerning craving and alcohol consumption. Both per-protocol and intention-to-treat analyses (PPA, ITTA) were conducted. Results: In both PPA and ITTA, significant group*time interaction effects were identified, whereby false-discovery-rate corrected post-hoc tests revealed that AAT0 most consistently reduced craving with stability towards follow-up. Results concerning alcohol consumption (g ethanol) were inconsistent. Conclusion: This study demonstrates that a simplified version of the imaginal retraining technique yields consistent results concerning craving reduction. This may hint towards the central importance of the core element of retraining: a movement of pushing (imagined) alcoholic beverages away. Possibly, more complex forms of imaginal retraining need further instruction than a written manual, such as instructive videos.